2021
DOI: 10.1155/2021/5527818
|View full text |Cite
|
Sign up to set email alerts
|

Barium Sulfate Scale Removal at Low-Temperature

Abstract: Precipitation of the scale in the oil and gas reservoirs, surface and subsurface equipment, and processing and production facilities is a big problem as it affects petroleum production. The scale precipitations decrease the oil and gas production and cause economical loss. Solving this issue requires an engineering investigation to provide a safe, efficient, and economic solution. Consequently, this study proposed a developed dissolver for barium sulfate scales, where two field-scale samples were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…Barium, calcium, magnesium and strontium were also reported at higher concentrations than other metals in the samples at 594 mg/L (4.33 mM), 5434 mg/L (135.60 mM), 2005 mg/L (82.51 mM) and 633 mg/L (7.22 mM), respectively. These high metal concentrations remain within the range reported in other oil reservoir formation waters [39][40][41].…”
Section: Formation Water Chemistrysupporting
confidence: 84%
“…Barium, calcium, magnesium and strontium were also reported at higher concentrations than other metals in the samples at 594 mg/L (4.33 mM), 5434 mg/L (135.60 mM), 2005 mg/L (82.51 mM) and 633 mg/L (7.22 mM), respectively. These high metal concentrations remain within the range reported in other oil reservoir formation waters [39][40][41].…”
Section: Formation Water Chemistrysupporting
confidence: 84%
“…We hypothesize that the time between militarized disputes is shortened when pairs of states experience rapid-onset disasters. 113 Hypothesis 7c: The climate change-related search for energy independence leads to the proliferation of civil nuclear programs and the increased risk of nuclear incidents that inadvertently escalate to interstate war.…”
Section: Increased Interstate Competition For Scarce Resourcesmentioning
confidence: 99%
“…Generally, pH-dependent scales are easier to treat than pH-independent scales. , This is because pH-dependent scales can be easily treated by acid injection, while this is not suitable for pH-independent scales . Thus, it is better to inhibit their occurrence, which can be achieved using chemical inhibitors such as chelating agents, ,, regulation of thermodynamic conditions of temperature and pressure, or by proper formulation of injected brine. , …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that sulfate scales can alter the surface properties and wetting behavior of rock surfaces. ,, Although an extensive body of literature is available for bulk precipitation reactions, , only a limited number of published articles , focus on the effect of scales on rock surface chemistry which greatly influences its wetting behavior. Nikoo and Malayeri examined sulfate scale/brine/rock interfacial interactions and the rock wettability due to CaSO 4 crystals.…”
Section: Introductionmentioning
confidence: 99%